The role of dissatisfaction and per capita income in explaining self-employment across 15 European countries - Niels Noorderhaven; A. Roy Thurik; Sander Wennekers; André J. van Stel (Max Planck Institute for Research into Economic Systems, 2004)
This paper deals with explaining the sizable differences in the rate of self-employment (business ownership) across 15 European countries in the period 1978-2000, within a framework of occupational choice, focusing on the influence of dissatisfaction and of per capita income. Using two different measures of dissatisfaction, in addition to the level of economic development and controlling for several other variables, we find that, in addition to a negative and significant impact of per capita income, dissatisfaction at the level of societies has a positive and significant influence on self-employment levels. Both dissatisfaction with life and dissatisfaction with the way democracy works are found to influence self-employment. It is concluded that these are proxies for job dissatisfaction and at the same time represent other negative 'displacements' known to promote self-employment. The findings indirectly point at the potential importance of push factors within the incentive structures of modern economies.
Keywords: M13; Z1; O57; P52; O11; 330; comparative analysis of economies; cultural economies; entrepreneurship; macroeconomic analyses of economic development; Selbstständige; Lebensqualität; Meinung; Sozialprodukt; Vergleich; Europa; Lebenszufriedenheit